Analysis Of Islamic Concept In Human Resource Management Practices - Susi Handayani Handayani; Yudi Siswadi (Proceeding International Seminar of Islamic Studies, 2019)
Indonesia is not a country that uses Islamic law, but the majority of the population is Muslim so most rules refer to Islamic rules. Even in daily life we carry out many Islamic rules, such as prayer, fasting, paying zakat and so on. Unwittingly at work, we also use the rules of Islam in the regulations made. This study aims to determine and analyze whether the concept of Islam is applied in Human Resource Management practices in companies in Indonesia. This article uses a qualitative description approach, focusing on current problems and phenomena. The author randomly extracts data and information from several employees who work at companies and study libraries to enrich writing. The results of research conducted indicate that there are several factors that are not in accordance with the concept of Islam, resulting in discomfort for Muslims who work there.The conclusion that can be drawn is that there is no coordination between the employees and policy makers dominated by those who are actually non-Muslims. Those who are non-Muslims always see Islam as a threat because they do not really know Islam, they still see Islam as that, rude, extreme and terrorist. Coupled with employees' ignorance with management, they prefer silence, accepting without protest every policy from the company for fear of being dismissed from the company.